2018
DOI: 10.3389/fmicb.2018.02226
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mast Cell Activation in Mongolian Gerbils Infected by Hepatitis E Virus

Abstract: Recently, mechanism study of hepatitis E virus (HEV) infection has attracted an increasing attention because of the growing rate of the acute hepatitis caused by the virus over the world. As an important initiate in the inflammation, mast cells (MCs) play a critical role in maintaining a healthy physiology. However, the function of the MCs in the acute hepatitis caused by HEV is still unclear. In the present study, mongolian gerbils infected by HEV were used as an animal model to evaluate the role of MCs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The gerbil model was also used to evaluate the role of mast cells during infection, which appear to increase upon disease progression in various liver disorders. It was demonstrated that the amount of mast cells increased in the liver and small intestines upon infection, as well as higher expression of tryptase and serotonin, which indicate activation of the cells [154].…”
Section: Other Small Animal Modelsmentioning
confidence: 99%
“…The gerbil model was also used to evaluate the role of mast cells during infection, which appear to increase upon disease progression in various liver disorders. It was demonstrated that the amount of mast cells increased in the liver and small intestines upon infection, as well as higher expression of tryptase and serotonin, which indicate activation of the cells [154].…”
Section: Other Small Animal Modelsmentioning
confidence: 99%
“…An immune-histological analysis of liver biopsies from HEV-infected acute liver failure patients showed that their cell counts of CD56+ were significantly higher than in biopsies from patients infected with HAV, HBV or HCV [110]. The number and the degree of activation of mast cells in Mongolian gerbils experimentally infected with HEV4 was also increased in both the liver and small intestine, suggesting that they are implicated in infection [111].…”
Section: Innate Immune Responsementioning
confidence: 96%
“…Med. 2020, 9, 331 9 of 25 activation of mast cells in Mongolian gerbils experimentally infected with HEV4 was also increased in both the liver and small intestine, suggesting that they are implicated in infection [111].…”
Section: Humoral and Cell-mediated Immune Responsesmentioning
confidence: 98%
“…Knowledge on further protagonists in cellular innate immune response to HEV infection is rare. Studies on HEV-infected Mongolian gerbils showed an enhanced activation of mast cells, a cell population largely associated with allergic reactions, but also regarded as a connection between innate and adaptive immune response [ 135 , 136 ]. Besides, histologic liver analyses of patients with acute HEV infection verified neutrophils as the predominant population in inflammatory cell infiltrates [ 137 ].…”
Section: Immune Responses Induced Against Hevmentioning
confidence: 99%